Laparoscopic management of liver abscess: a viable alternative in USG guided percutaneous drainage failure cases - Tak, Nikhil; Bagree, Rajendra; Jalendra, Gaurav; Reddy, Hetish M. (International Surgery Journal, 2021)
Background: Liver abscesses are conventionally treated by ultrasonography (USG) guided percutaneous aspiration or drainage under antibiotic cover. We performed laparoscopic liver abscess drainage successfully in patients where medical management and percutaneous drainage had proven inadequate. Methods: Cases were received either from outpatient department (OPD) or were transferred from medical wards. Patients were first treated conservatively and percutaneous aspiration was attempted. Patients not responding to these treatment modalities were considered for diagnostic laparoscopy with drainage of abscess cavity and placement of 28 Fr drain under vision. Results: 20 patients with large liver abscess were treated successfully by laparoscopic drainage. Mean age in the study was 47 years (range 19-70 years) and average hospital stay was 5 days (range 4-12 days). Major postoperative morbidity or deaths were not registered. Patients with ruptured liver abscess, deep seated abscess cavity and medically unfit patients were excluded from the study. Conclusions: Laparoscopic drainage of liver abscesses, in combination with systemic antibiotics is a safe and viable alternative in all patients who require surgical drainage. It helps in the early return of gastrointestinal function and resumption of normal activities also potentially achieving better abscess drainage.